Remain : a supernatural love story [large type] - Sparks, Nicholas; Shyamalan, M. Night (Random House Large Print, 2025)
"When New York architect Tate Donovan arrives in Cape Cod to design his best friend's summer home, he is hoping to make a fresh start. Recently discharged from an upscale psychiatric facility where he was treated for acute depression, he is still wrestling with the pain of losing his beloved sister. Sylvia's deathbed revelation--that she can see spirits who are still tethered to the living world, a gift that runs in their family--sits uneasily with Tate, who strugglesto believe in more than what reason can explain. But when he takes up residence at a historic bed-and-breakfast on the Cape, he encounters a beautiful young woman named Wren who will challenge every assumption he has about his logical and controlled world. Tate and Wren find themselves forging an immediate connection, one that neither has ever experienced before. But Tate gradually discovers that below the surface of Wren's idyllic small-town life, hatred, jealousy, and greed are festering, threatening their fragile relationship just as it begins to blossom. Tate realizes that in order to free Wren from an increasingly desperate fate, he will need to unearth the truth about her past before time runs out ... a quest that will make him doubt whether we can ever believe the stories we tell about ourselves, and the laws that govern our existence. Love--while transformative--can sometimes be frightening."--Provided by publisher.